Body mass and cell size shape the tolerance of fishes to low oxygen in a temperature‐dependent manner - Wilco C. E. P. Verberk; Jeroen F. Sandker; Iris L. E. van de Pol; Mauricio A. Urbina; Rod W. Wilson; David J. McKenzie; Félix P. Leiva (Global Change Biology, 2022)
Aerobic metabolism generates 15–20 times more energy (ATP) than anaerobic metabolism, which is crucial in maintaining energy budgets in animals, fueling metabolism, activity, growth and reproduction. For ectothermic water‐breathers such as fishes, low dissolved oxygen may limit oxygen uptake and hence aerobic metabolism. Here, we assess, within a phylogenetic context, how abiotic and biotic drivers explain the variation in hypoxia tolerance observed in fishes. To do so, we assembled a database of hypoxia tolerance, measured as critical oxygen tensions ( P crit ) for 195 fish species. Overall, we found that hypoxia tolerance has a clear phylogenetic signal and is further modulated by temperature, body mass, cell size, salinity and metabolic rate. Marine fishes were more susceptible to hypoxia than freshwater fishes. This pattern is consistent with greater fluctuations in oxygen and temperature in freshwater habitats. Fishes with higher oxygen requirements (e.g. a high metabolic rate relative to body mass) also were more susceptible to hypoxia. We also found evidence that hypoxia and warming can act synergistically, as hypoxia tolerance was generally lower in warmer waters. However, we found significant interactions between temperature and the body and cell size of a fish. Constraints in oxygen uptake related to cellular surface area to volume ratios and effects of viscosity on the thickness of the boundary layers enveloping the gills could explain these thermal dependencies. The lower hypoxia tolerance in warmer waters was particularly pronounced for fishes with larger bodies and larger cell sizes. Previous studies have found a wide diversity in the direction and strength of relationships between P crit and body mass. By including interactions with temperature, our study may help resolve these divergent findings, explaining the size dependency of hypoxia tolerance in fish.